2021
DOI: 10.3390/jcm10071362
|View full text |Cite
|
Sign up to set email alerts
|

The GERtality Score: The Development of a Simple Tool to Help Predict in-Hospital Mortality in Geriatric Trauma Patients

Abstract: Feasible and predictive scoring systems for severely injured geriatric patients are lacking. Therefore, the aim of this study was to develop a scoring system for the prediction of in-hospital mortality in severely injured geriatric trauma patients. The TraumaRegister DGU® (TR-DGU) was utilized. European geriatric patients (≥65 years) admitted between 2008 and 2017 were included. Relevant patient variables were implemented in the GERtality score. By conducting a receiver operating characteristic (ROC) analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The FFI is associated with an increased risk of complications. This result is in accordance with previous studies on geriatric trauma patients and their complication predictions with the FFI [24,[36][37][38][39][40]. In the literature, the FFI has also been shown to be predictive of the development of pneumonia [41,42].…”
Section: Plos Onesupporting
confidence: 91%
“…The FFI is associated with an increased risk of complications. This result is in accordance with previous studies on geriatric trauma patients and their complication predictions with the FFI [24,[36][37][38][39][40]. In the literature, the FFI has also been shown to be predictive of the development of pneumonia [41,42].…”
Section: Plos Onesupporting
confidence: 91%
“…Many studies have shown that a low GCS score is associated with poor prognosis in elderly patients with trauma, as shown in the present study. 33 , 34 However, it is difficult to predict prognosis with the GCS because it does not involve brainstem reflexes, nor does it accurately describe the verbal status of intubated patients. In particular, in elderly patients with trauma, the measurement of the GCS motor response can be inaccurate, requiring more careful measurement.…”
Section: Discussionmentioning
confidence: 99%
“…The new GERtality score seems to be an userfriendly and adequate in-hospital mortality prediction model for severely injured geriatric trauma patients, as it includes only five easily assessable patient variables, which makes it practical and simple to calculate. However, further studies should validate the novel GERtality score on different datasets [66].…”
Section: Summary Of Evidence and Discussionmentioning
confidence: 99%